ANALISIS PERTANGGUNGJAWABAN PIDANA OLEH ANAK YANG MELAKUKAN TINDAK PIDANA PENCABULAN TERHADAP ANAK DITINJAU DARI ASPEK KEMANFAAATAN HUKUM - Fatemaluo, Kartini (Jurnal Panah Hukum, 2025)
The crime of sexual immorality is an unlawful act committed by a man against a woman with violence or threats of violence that does not have a legal relationship. This criminal act of sexual immorality was committed by a child against a child which had a negative impact which was tried by a panel of judges at the Sumenep District Court, namely Decision Number: 6/Pid.Sus-Anak/2017/PN Smp, In this decision the Judge decided that the defendant was legally proven and convicted of committing a criminal act by intentionally committing violence, forcing a child to have sexual intercourse with him. Sentenced to prison for 3 years and 6 months for job training at the Sumenep work center. This research is entitled analysis of criminal responsibility by children who commit criminal acts of sexual abuse against children in terms of the legal benefit aspect (Decision Study Number 6/Pid.Sus-Anak/2017/PN Smp). The type of research used is normative legal research using the statutory approach, case approach and analytical approach. Data collection was carried out using secondary data through primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is descriptive qualitative analysis and conclusions are drawn using a deductive method. Based on the research findings and discussion, it can be concluded that the prison sentence of 3 years and 6 months work training for the defendant does not have a legal beneficial impact on the victim who has become a victim of violence and has even given birth to a child from the defendant's actions, the judge did not pay attention to the principle of legal benefit. This is so that it is accepted by victims and the community, where the hope for law enforcement in Indonesia is carried out not only by paying attention to the legal aspects but also to social aspects that can be accepted and felt by victims or the community, such as providing restitution and recovery. Researchers are of the opinion that it is better to punish perpetrators of this crime by paying more attention to aspects of benefit for child victims, not just providing a deterrent effect or legal retaliation against the defendant.